(untitled) (Research, Society and Development, 2021)
Drug use within students has been rising over the years. The objective of this study was to evaluate drug consumption and the knowledge about its consequences among Odontology’s student population in Recife and the Metropolitan area. This is a descriptive, cross-sectional study of a quantitative and qualitative approach, with 210 students of the first and last semesters of public and private schools in Pernambuco participated in the study. In this study, three questionnaires were used: one with the social indicators, another one for drug use, and the last one about knowing the consequences of using alcohol, marijuana and cocaine consumption. Statistic descriptive, Pearson Qui-square, and student T-test were used to analyze the data. It was observed that life time drug use was 81,90% of alcohol beverages, 25,24% tobacco products, 24,76% marijuana, 10,48% inhalants, 7,14% hypnotics or sedatives, 5,71% hallucinogens, 4,76% amphetamines or ecstasy, 3,33% cocaine e 1,43% opioids. For the consequence’s awareness, it was observed 96,67% obtained more than half of the correct answers regarding alcohol, 87,14% for marijuana and 90,95% for cocaine. There is a high prevalence of drug use and a good level of knowledge about the consequences of alcohol, marijuana, cocaine use among universities students.